An Examination of Audio-visual Effects on Memory Capacity of Production Workers Based on Educational Targets - Kurniawan, Juliadi; Tubagus, Putra; Domingus, Rafael (Journal of Multimedia Trend and Technology, 2024)
Humans have two different types of memory: short-term memory and long-term memory. Information is momentarily stored in short-term memory before being transferred to long-term memory. A string of characters, numbers, colours, or names that can be spoken or presented in less than two seconds can be stored in short-term memory. Many work environments overwhelm workers; for instance, a tailor may be able to maximise productivity if he works while listening to music. One of the things that can affect the workplace is audio-visual. Humans differ in how old their short-term memory is. Those who are still productive tend to have stronger memories than those who are older. The purpose of this study is to ascertain, in light of educational attainment, how audio-visuals affect short-term memory in adults of working age. Because it can still use short-term memory to effectively receive, process, and communicate information in a work environment, productive age is used. The results of an analysis conducted using Work Design software and Design Tools for Methods Standard indicated that the mistake rate at the productive age level at the undergraduate education level had a greater impact than it did at the high school level. This may be the result of short-term memory loss brought on by ageing.